2015
DOI: 10.1111/febs.13330
|View full text |Cite
|
Sign up to set email alerts
|

Silicon‐based quantum dots induce inflammation in human lung cells and disrupt extracellular matrix homeostasis

Abstract: Quantum dots (QDs) are nanocrystalline semiconductor materials that have been tested for biological applications such as cancer therapy, cellular imaging and drug delivery, despite the serious lack of information of their effects on mammalian cells. The present study aimed to evaluate the potential of Si/SiO 2 QDs to induce an inflammatory response in MRC-5 human lung fibroblasts. Cells were exposed to different concentrations of Si/SiO 2 QDs (25-200 lgÁmL À1 ) for 24, 48, 72 and 96 h. The results obtained sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 72 publications
4
21
0
Order By: Relevance
“…Smad3 is involved in a series of pathophysiological alterations, including the increase of cerebral microvessel permeability, aseptic inflammation, blood-brain barrier damage and encephaledema (19). Synthetic Smad3 inhibitors may inhibit these alterations to some extent (20). The present study demonstrated that oxymatrine significantly reduced Smad3 protein levels when compared with the model group.…”
Section: Discussionsupporting
confidence: 47%
“…Smad3 is involved in a series of pathophysiological alterations, including the increase of cerebral microvessel permeability, aseptic inflammation, blood-brain barrier damage and encephaledema (19). Synthetic Smad3 inhibitors may inhibit these alterations to some extent (20). The present study demonstrated that oxymatrine significantly reduced Smad3 protein levels when compared with the model group.…”
Section: Discussionsupporting
confidence: 47%
“…Therefore, IL-8 could more easily penetrate through confluent cell layer and the insert membrane. Besides, from the basal fibroblasts the contribution to the basal medium were probably higher from IL-8 compared to MMP-9 [28]. A third explanation for this could also be that there were differences in the direction of secretion between IL-8 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…Malondialdehyde (MDA) concentration was determined as a marker of lipid peroxidation using the fluorimetric method described previously by our group [ 81 ]. Thus, 200 µL of cell lysate, correspondingly diluted, were mixed with a volume of 700 µL of 0.1 N HCl and incubated at room temperature for 20 min.…”
Section: Methodsmentioning
confidence: 99%